IMPLEMENTATION OF THE ROLE OF THE PROSECUTION IN EFFORTS TO MANAGE PROOF EVIDENCE CRIMINAL ACTS OF CORRUPTION - Ferry Irmawan; Yasmirah Mandasari Saragih; Ahmad Novaisal; Riki Hamdani; Sony Prayudha Winata (RADJA PUBLIKA, 2023)
The prosecutor's office is the only state institution which is a government apparatus that has the authority to delegate criminal cases, prosecute perpetrators of criminal acts in court and carry out decisions and decisions of criminal judges. This power is a characteristic of the prosecutor's office which differentiates it from other law enforcement institutions or agencies. other. In implementing the Judge's decision, the Prosecutor has the authority to execute the evidence by destroying or confiscating it for the benefit of the state or returning the evidence to its rightful owner in accordance with the decision determined by the Panel of Judges. In the event of confiscation of evidence for state interests, the Indonesian Prosecutor's Office also plays a role in managing the evidence. The prosecutor's office uses several methods or mechanisms to manage this evidence, which in practice is very important and crucial, especially in the use and income of state treasury. Based on the research results, it was found that regarding the management of evidence obtained by investigators, it cannot necessarily be managed by the prosecutor's office, but rather has a process so that it can ultimately be confiscated for the state and managed by the prosecutor's office. This process is important for the internal bureaucracy of the Prosecutor's Office as well as the transparency and efficiency of the work carried out by the Prosecutor's Office.